Research of the Shift Schedule and Ratio Optimization for the Transmission System of a Two-speed Electric Vehicle - Zhou Yunshan; Yang Kefeng (Jixie chuandong)
In order to improve the power performance and fuel economy of the electric vehicle,the transmission ratio optimization design for a two- speed electric vehicle transmission system is studied. The 0 80km / h acceleration time and hundred kilometers power consumption are respectively taken as two sub- objective functions for dynamics and economic performance. A speed ratio optimization model for the dual objective functions is built. Taking the coupling effect of the shift schedule in optimization process into account,the rule of developing a comprehensive shift strategy,which associates with ratios and considers the dynamic and economic performances is determined. An enumeration algorithm,which has the function of non- dominated comparing and filtering,is designed to obtain the Pareto- optimal solution set for the dual objective function. Finally the proposed electric vehicle with a set of the optimal ratio solutions is compared with this vehicle with the initial ratios. The results show that the acceleration time is shortened by 3. 5% and the energy consumption is decreased by 2. 4%,the power performance and fuel economy of the electric vehicle are improved.